Associations of sleep duration with neurocognitive development in the first 2 years of life. (23rd January 2022) - Cao, Shuting; Liu, Juan; Li, Yuanyuan; Xu, Shunqing; Xia, Wei
Summary: The effect of sleep duration on neurocognitive development in infants and toddlers remains unclear. We aimed to investigate the relationship between sleep duration and neurocognitive development in infancy. Based on a prospective birth cohort, 2220 mother–infant pairs were enrolled in Wuhan, China, between January 2014 and October 2017. Sleep duration was evaluated at 1, 6, 12 and 24 months via parent‐report questionnaires. To assess the children's neurocognitive development at 2 years old, the Bayley Scales of Infant Development of China Revision was used to assess the Mental Development Index (MDI) and Psychomotor Development Index (PDI). A group‐based semiparametric mixture model was used to estimate the developmental trajectories of the total, nighttime and daytime sleep duration. The associations of sleep duration at each age and sleep duration trajectories with Mental Development Index scores and Psychomotor Development Index scores were analysed using generalized linear models. Daytime sleep duration (≥ 10.0 hr) at 1 month was associated with lower Mental Development Index scores ( β  = −3.55, 95% confidence interval: −6.02, −1.08) and lower Psychomotor Development Index scores ( β  = −2.87, 95% confidence interval: −4.94, −0.81). Nighttime sleep duration (≤ 7.0 hr) at 6 months was associated with lower Mental Development Index scores ( β  = −7.02, 95% confidence interval: −11.02, −3.01). Daytime sleep duration (> 4 hr) and nighttime sleep duration (< 8 hr) at 12 months were associated with lower Mental Development Index scores ( β  = −9.17, 95% confidence interval: −15.35, −2.98) and lower Psychomotor Development Index scores ( β  = −8.14, 95% confidence interval: −13.56, −2.71), respectively. In further sleep duration trajectories analyses, lower Mental Development Index scores were significantly associated with the "decreased and then increased nighttime sleepers" trajectory ( β  = −4.39, 95% confidence interval: −8.02, −0.76), and "long and decreased daytime sleepers" trajectory ( β  = −2.44, 95% confidence interval: −4.58, −0.30). These results showed that short nighttime sleep duration and long daytime sleep duration in infancy were detrimental to children's neurocognitive development.